2003
DOI: 10.1177/0899764003257462
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition, Committees, and Organizational Efficiency: The Case of Nonprofits

Abstract: This article investigates the relationship between nonprofit board composition and organizational efficiency. Overall,we find a significant statistical association between the presence of major donors on the board and indicators of organizational efficiency. Although causality cannot be demonstrated,our findings are consistent with the Fama and Jensen (1983) conjecture that major donors monitor nonprofit organizations at least in part through their board membership. The multivariate analysis shows that the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
199
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(219 citation statements)
references
References 33 publications
12
199
1
7
Order By: Relevance
“…In such case, no improvement will be found. Although empirical research by Callen and Falk (1993) did not reveal that board composition significantly influenced the board' s technical or allocating efficiency, Callen, Klein, and Tinkelman (2003) found that an increase in the proportion of major donors on the board lowered the proportion of administrative expenses to total expenses and raised the proportion of program expenses to total expenses.…”
Section: Caers Du Bois Jegers De Gieter Schepers Pepermansmentioning
confidence: 95%
“…In such case, no improvement will be found. Although empirical research by Callen and Falk (1993) did not reveal that board composition significantly influenced the board' s technical or allocating efficiency, Callen, Klein, and Tinkelman (2003) found that an increase in the proportion of major donors on the board lowered the proportion of administrative expenses to total expenses and raised the proportion of program expenses to total expenses.…”
Section: Caers Du Bois Jegers De Gieter Schepers Pepermansmentioning
confidence: 95%
“…In support of fundraising success as criteria for NPO effectiveness, Callen [19] postulates that fund raising expenditures are equivalent to advertising expenditures in the corporate sector. Despite administration and fund raising, Callen, Klein and Tinkelman [20] found that there is a correlation between governance and efficiency in NPOs, thereby confirming that NPO governance issues are criteria for the determination of effectiveness. Major donors assess the effectiveness of NPOs based on the composition of their Board [17].…”
Section: Organisational Effectiveness For Non-profit Institutionsmentioning
confidence: 97%
“…This program expense ratio measures the efficiency with which total expenses are made toward production of the charitable good (programs) instead of being used for fundraising and administration. The program expense ratio is a widely used measure of efficiency in NFPs (e.g., Weisbrod and Dominguez, 1986;Posnett and Sandler, 1989;Tinkelman, 1998 and1999;Baber, Daniel and Roberts, 2002;Krishnan, Yetman and Yetman, 2004), and has been used in prior studies examining the relation between governance quality and NFP performance (e.g., Callen, Klein, and Tinkelman, 2003;Desai and Yetman, 2005). If excess endowments signal better monitoring, we expect a positive, or no, relation between excess endowments and the program expense ratio.…”
mentioning
confidence: 99%